Housing for Young – New Ideas - Tokajuk, Andrzej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
This article presents the results of research conducted at the Faculty of Architecture of the Bialystok University of Technology. The aim of the research was to develop a concept of accessible housing for young people, with the implementation of a modular method of implementing such housing structures. The methods of work adopted were "research by design" and analytical method which was used to analyze the literature on contemporary standards of affordable housing and modular structures. The choice of modular technology was dictated by the need to reduce the costs of erecting buildings and housing structures as well as the aspects of energy efficiency and sustainable development.